Serum Malondialdehyde Level as a Risk Factor for Threatened Abortion - Gusti N Sutama; I Gede P Surya (Indonesian Socety of Obstetrics and Gynecology, 2015)
Objective: To determine the role of serum malondialdehyde level as a risk factor for threatened abortion. Method: Our study was a caseâ€control study. We examined 60 pregnant women as our subject, 30 subjects with threatened abortion as cases and 30 subjects with normal pregnancy as control group. Serum levels of malondialdehyde of each woman was examined in the Biochemistry Laboratory Faculty of Medicine Gadjah Mada University in Yogyakarta. We tested the normality of our data using Kolmogorovâ€ Smirnov test, and analysis was then performed using independent sample tâ€test. To determine the relationship of serum malondialdehyde with threatened abortion, Chiâ€Square test was used. Result: From this study we found that the average serum malondialdehyde level in threatened abortion was 1.33K0.11 nmol/ml, while the average level of serum malondialdehyde in normal pregnancy was 1.03K0.10 nmol/ml. The analysis using independent tâ€test shows that the average serum malondialdehyde level on the two groups was significantly different (p=0.001). Based on the cutâ€off value of 1.12 nmol/ml, we found that the relative risk of threatened abortion is 29.57 times (95% CI=6.85â€127.64, p=0.001) in those with a high level of serum malondialdehyde. Conclusion: The serum malondialdehyde level in threatened abortion was significantly different compared to normal pregnancy. A high level of serum malondialdehyde in pregnancy was a risk factor for threatened abortion. Keywords: malondialdehyde, normal pregnancy, threatened abortion